Sejarah Pendidikan Indonesia Masa Orde Baru: Menguak Keberhasilan dan Kegagalan Kebijakan Pemerintah Orde Baru dalam Bidang Pendidikan - Ramadhan, Fauzan Syahru; Anggoro, Nur Ramadhani Catur; Pramono, Muhammad Setyo; Indradaffa, Garin Ahmad (CHRONOLOGIA, 2024)
This article focuses on the success and failure of policies implemented by the Government of the Republic of Indonesia, especially during the New Order government in the field of Education. There are many problems in the field of education that occurred during the New Order, such as the problem of equitable distribution of education, improving the quality, effectiveness, efficiency, and relevance of education to national development. Therefore, this article aims to find out how the response of the New Order government in dealing with educational problems that can be quickly resolved. This article uses historical methods that include heuristics, criticism, interpretation, and historiography. The results of this article show that the policies taken by The New Order government have an orientation to improve public welfare and solve problems in the field of education, but not all policies taken in the implementation process run well and smoothly. There are policies that in the process of implementation actually failed.